Genetic variations in S gene of porcine epidemic diarrhoea virus from 2018 in Sichuan Province, China. Issue 4 (4th September 2020) - Li, Fei; Zeng, Yubing; Zhang, Rubo; Peng, Kenan; Jiang, Chaoyuan; Xu, Zhiwen; Zhu, Ling
Abstract: Porcine epidemic diarrhoea virus (PEDV) belongs to the family Coronavirus, a genus of coronavirus, a highly contact‐infectious intestinal disease pathogen. In this study, we downloaded 62 PEDV S gene sequences uploaded to GenBank, including 10 uploaded by our laboratory from 2018, and constructed a PEDV S gene evolution tree using MEGA V7.0 software. Phylogenetic tree analysis indicated that the genogroup of PEDV in Sichuan Province was divided into three coexisting genogroups (GII‐a, GII‐b and GI‐a), of them, GII‐a has become the main genogroup in the province due to its prevalence and range of spread. Amino acid sequence analysis showed that there were amino acid insertions and deletions in the S protein encoded by the amplified S gene, and there were amino acid mutations in the COE and SS6 of the epitope in the amplified S protein. These results provide a basic research theory for understanding the prevalence of PEDV variation and controlling PED in Sichuan. Abstract : In 2018, 10 strains of PEDV S gene were amplified in Sichuan. The genetic evolution analysis of 10 strains of PEDV and the reference strain showed that GII‐a was the main strain in Sichuan. Provide reference for PEDV prevention and control in Sichuan.